Comparison of oral metabolome profiles of stimulated saliva, unstimulated saliva, and mouth-rinsed water - Maruyama, Yuki; Nishimoto, Yuichiro; Umezawa, Kouta; Kawamata, Ryosuke; Ichiba, Yuko; Tsutsumi, Kota; Kimura, Mitsuo; Murakami, Shinnosuke; Kakizawa, Yasushi; Kumagai, Takashi; Yamada, Takuji; Fukuda, Shinji (Scientific reports, 2022)
Saliva includes a substantial amount of biological information, which has enabled us to understand the relationship between oral metabolites and various oral and systemic disorders. However, collecting saliva using a controlled protocol is time-consuming, making saliva an unsuitable analyte in large cohort studies. Mouth-rinsed water (MW), the water used to rinse the mouth, can be collected easily in less time with less difference between subjects than saliva and could be used as an alternative in oral metabolome analyses. In this study, we investigated the potential of MW collection as an efficient alternative to saliva sample collection for oral metabolome profiling. MW, stimulated saliva, and unstimulated saliva were collected from 10 systemically healthy participants. The samples were subjected to metabolome analysis using capillary electrophoresis time-of-flight mass spectrometry, and the types and amounts of metabolites in the samples were compared. Qualitatively, MW contained the same metabolites as unstimulated and stimulated saliva. While the quantity of the metabolites did not drastically change between the sampling methods, all three reflected individual differences, and the features of MW were the same as those of the unstimulated saliva. Overall, these results suggest that MW may be an appropriate alternative to saliva in oral metabolome profile analysis.